Exposure to toxic waste sites: an investigative approach. - Stehr-Green, P A (1989)
Improper dumping and storage of hazardous substances and whether these practices produce significant human exposure and health effects are growing concerns. A sequential approach has been used by the Centers for Disease Control and the Agency for Toxic Substances and Disease Registry in investigating potential exposure to and health effects resulting from environmental contamination with materials such as heavy metals, volatile organic compounds, and pesticide residues at sites throughout the United States. The strategy consists of four phases: site evaluation, pilot studies of exposure or health effects, analytic epidemiology studies, and public health surveillance. This approach offers a logical, phased strategy to use limited personnel and financial resources of local, State, national, or global health agency jurisdictions optimally in evaluating populations potentially exposed to hazardous materials in waste sites. Primarily, this approach is most helpful in identifying sites for etiologic studies and providing investigative leads to direct and focus these studies. The results of such studies provide information needed for making risk-management decisions to mitigate or eliminate human exposures and for developing interventions to prevent or minimize health problems resulting from exposures that already have occurred.